Pathophysiological basis of human papillomavirus in penile cancer: Key to prevention and delivery of more effective therapies. (17th June 2016) - Spiess, Philippe E.; Dhillon, Jasreman; Baumgarten, Adam S.; Johnstone, Peter A.; Giuliano, Anna R.
ABSTRACT: Answer questions and earn CME/CNE Squamous cell carcinoma (SCC) of the penis is a rare malignancy in the United States, with a significantly higher incidence—up to 20 to 30 times greater—in areas of Africa and South America. This can be explained in part by the significantly greater prevalence of sexually transmitted diseases among high‐risk males often having unprotected sex with multiple sexual partners. Human papillomavirus (HPV) has been implicated as the infectious pathway by which several these penile neoplasms originate from precursor lesions. In this regard, a fundamental understanding of HPV in penile carcinogenesis can have meaningful implications in understanding 1) the diagnosis of HPV‐related precursor penile lesions, 2) targeting HPV‐specific molecular pathways, and 3) cancer prevention. Using vaccination programs not only may improve patient outcomes but also may minimize the need for highly aggressive and often debilitating surgical resection.CA Cancer J Clin 2016;66:481–495. © 2016 American Cancer Society .